The first report of single nucleotide polymorphisms in the open reading frame of the prion-like protein gene in rabbits - Jeong, Min-Ju; Kim, Yong-Chan; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2024)
Background: Natural cases of prion disease have not been reported in rabbits, and prior attempts to identify a prion conversion agent have been unsuccessful. However, recent applications of prion seed amplifying experimental techniques have sparked renewed interest in the potential susceptibility of rabbits to prion disease infections. Among several factors related to prion disease, polymorphisms within the prion-like protein gene (PRND), a member of the prion protein family, have been reported as significantly associated with disease susceptibility in various species. Therefore, our study aimed to investigate polymorphisms in the PRND gene of rabbits and analyze their genetic characteristics. Methods: Genomic DNA was extracted from 207 rabbit samples to investigate leporine PRND polymorphisms. Subsequently, amplicon sequencing targeting the coding region of the leporine PRND gene was conducted. Additionally, linkage disequilibrium (LD) analysis was employed to assess the connection within and between loci. The impact of non-synonymous single nucleotide polymorphisms (SNPs) on the Doppel protein was evaluated using PolyPhen-2. Results: We found nine novel SNPs in the leporine PRND gene: c.18A>G, c.76G>C, c.128C>T, c.146C>T, c.315A>G, c.488G>A, c.525G>C, c.544G>A, and c.579A>G. Notably, seven of these PRND SNPs, excluding c.525G>C and c.579A>G, exhibited strong LD values exceeding 0.3. In addition, LD analysis confirmed a robust link between PRNP SNP c.234C>T and PRND SNPs at c.525G>C and c.579A>G. Furthermore, according to PolyPhen-2 and SIFT analyses, the four non-synonymous SNPs were predicted to have deleterious effects on the function or structure of the Doppel protein. However, PANTHER and Missense3D did not indicate such effects. Conclusion: In this paper, we have identified novel SNPs in the rabbit PRND gene and predicted their potential detrimental effects on protein function or structure through four non-synonymous SNPs. Additionally, we observed a genetic linkage between SNPs in the PRND and PRNP genes. These findings may provide insights into understanding the characteristics of rabbits as partially resistant species. To the best of our knowledge, this study is the first to genetically characterize PRND SNPs in rabbits.